Wrist-ankle acupuncture for primary dysmenorrhea: a randomized controlled trial evaluating the efficacy of an analgesic strap - Zhai, Shujie; Wang, Chenmiao; Ruan, Yi; Liu, Yue; Ma, Rui; Fang, Fanfu; Zhou, Qinghui (Frontiers in Neurology, 2024)
Background Drawing on the principles of wrist-ankle acupuncture (WAA), our research team has developed a portable device for WAA point compression, termed the acupressure wrist-ankle strap (AWA). The current study aims to evaluate the efficacy of the AWA in alleviating pain associated with primary dysmenorrhea. Methods A single-blind, randomized clinical trial was conducted from April 1, 2019, to December 31, 2019. 78 participants with primary dysmenorrhea were recruited from Shanghai University of Traditional Chinese Medicine. All participants were treated on the first day of menstruation for 30 min. Participants in the AWA group used the AWA, the internal side of which is equipped with a tip compression component, while participants in the non-acupressure wrist-ankle acupuncture(NAWA)group used the NAWA, with the inside tip pressing parts removed. The main outcome was the difference in visual analogue scale (VAS) score between baseline and 30 minutes after randomization. Results A total of 78 participants aged 18 to 30 years were included in the intention-to-treat analyses. The VAS scores (mean [standard deviation]) in the AWA group were significantly lower than those in the NAWA group at each time point of intervention (5 minutes: 95% CI, [−1.27 to −0.68], p < 0.001; 10 minutes: 95% CI, [−2.34 to −1.51], p < 0.001; 30 minutes: 95% CI, [−3.74 to −2.72], p < 0.001). In the AWA group, 16 participants reported “obvious relief” of dysmenorrhea pain while 23 did not; the average onset time of analgesia they reported were (21.50 ± 3.65) min, while no subjects in NAWA group reported obvious pain relief. The pain threshold (mean [standard deviation]) at SP9 of both sides in AWA group decreased significantly after intervention that in NAWA group (Left: 95% CI, [−5.02 to −1.81], p < 0.001; Right: 95% CI, [−7.67 to −4.24], p < 0.001). There was no significant change in the temperature at CV4 in either group (95% CI, [−0.63 to −0.66], p = 0.970). Conclusion This trial substantiates our hypothesis that the AWA provides immediate analgesic effects. The AWA represents an effective and safe non-invasive physical therapy option, which patients can self-administer to alleviate abdominal pain